Synthetic Fuels from Biomass: Photocatalytic Hydrodecarboxylation of Octanoic Acid by Ni Nanoparticles Deposited on TiO2. Issue 2 (8th December 2021) - Du, Xiangze; Peng, Yong; Albero, Josep; Li, Dan; Hu, Changwei; García, Hermenegildo
Abstract: Decarboxylation of low‐value fatty acids from biomass is a simple process to produce synthetic fuels suitable to be blended with gasoline or diesel. The present study reports the photocatalytic decarboxylation of octanoic acid in the presence of H2 by a series of modified TiO2 to form mixtures of n ‐heptane and tetradecane as major products in variable proportions, depending on the photocatalyst and the reaction conditions. It was found that the photocatalytic activity increases upon an optimal reductive NaBH4 treatment, presumably by generation of surface oxygen vacancies and by the deposition of Ni nanoparticles in the appropriate loading. Under the optimized conditions, an almost complete octanoic acid conversion and a combined selectivity to n ‐heptane and tetradecane over 80 % were reached at 10 h of UV/Vis light irradiation with a 300 W Xe lamp. No changes in the photocatalytic performance were observed for six consecutive runs. The present results illustrate the possibility that photocatalytic decarboxylation offers for the transformation of biomass into synthetic fuels under mild conditions. Abstract : Shine a light : Upon irradiation with UV light, a Ni/TiO2 photocatalyst rich in oxygen atom vacancies promotes photodecarboxylation of octanoic acid with a high selectivity to heptane and tetradecane.